USE OF TECHNICAL METHODS IN THE DEVELOPMENT OF SPEED QUALITIES OF GIRLS ENGAGED IN JUDO (Scientific journal of the Fergana State University, 2024)
The practical significance of the research results in this scientific research work is that the main methods used by judo girls, the movements used in the competition and their individual characteristics have been determined, and the results are based on the technical methods for developing the main methods that are often used during the competition. it is explained by the fact that it is possible to introduce the recommendations into the training process.